HDAC3-Regulated PGE2 Production by Microglia Induces Phobic Anxiety Susceptibility After Stroke and Pointedly Exploiting a Signal-Targeted Gamma Visual Stimulation New Therapy - Zhu, Hongrui; Guo, Yi; Huang, Ailing; Shen, Huidan; Chen, Yang; Song, Jingyi; Guan, Ao; Wu, Liang; Wang, Huiting; Deng, Bin (Frontiers in Immunology, 2022)
Background: Phobic anxiety present after stroke (called poststroke anxiety, PSA) can hamper the rehabilitation of patients and disrupt their usual activities. Besides, the symptoms and mechanisms of PSA are different from those in nonstroke populations that have generalized anxiety disorder. What’s more, the treatment approaches for phobic anxiety are confined to unitary or general methods with poor efficiency. Methods: Behavioural test screen combined bioinformatics analysis explored molecular changes between generalized anxiety disorder in nonstroke mice (restraint stress, RS) and photothrombotic stroke mice exposed to environmental stress (PTS + RS, mimicking PSA). Multiple molecular biological and neurobiological methods were employed to explain mechanisms in vitro and in vivo. And exploiting gamma flicker stimulation device for therapy. Results: Microglial (MG) overactivation is a prominent characteristic of PTS + RS. HDAC3 was mainly upregulated in activated-microglia from damaged cortex and that local prostaglandin E2 (PGE2) production increased in MG via HDAC3-mediated activation of NF-κB signalling by p65 deacetylation. A high content of PGE2 in damaged ischaemic cortex could diffuse freely to amygdala, eliciting anxiety susceptibility of PSA via EP2. Importantly, gamma flicker stimulation relieved anxious behaviour of PTS + RS by modulating the HDAC3/Cox1/EP2 network at some extent. Conclusions: HDAC3-regulated PGE2 production by microglia constitutes phobic anxiety susceptibility after stroke and a protective approach of gamma visual stimulation can be a candidate new therapy.